A classe trabalhadora in movimento um retrato das lutas dos trabalhadores no Jornal Movimento (1975-1981) - Castilho, Eribelto Peres (2016)
This study aims to provide a critical analysis of the image, of the opposition, defeats, struggles and victories usual in the working class life during the period of 1975 to 1981, pictured in the pages of Movimento newspaper. The timeline proposed in our study – that cover the period that Movimento was published (1975-1981) – can be considered one of the most significant in Brazil’s recent history. The 1970’s and beginning of the 1980’s represent a moment of intense and profound social contradictions, resulting in changes in the country’s cultural, political and economical panorama. This period is marked (acknowledged) by the vigorous and acute reemerging of the working class in the social scenario. And as a sign of resistance and struggle the targeted their actions against the cut down, exploration and autocracy, therefore demonstrating, to everyone’s surprise, that they were not asleep, as they never had been even during the terrible years of the dictatorship. These years of important social changes are an adequate and essencial period for the understanding of the working class unique and shared experiences